Isolating the effect of soil properties on agricultural soil greenhouse gas emissions under controlled conditions. (24th October 2019) - Miller, Gemma A.; Rees, Robert M.; Griffiths, Bryan S.; Cloy, Joanna M.
Abstract: Agricultural soils are important sources of greenhouse gases (GHGs). Soil properties and environmental factors have complex interactions which influence the dynamics of these GHG fluxes. Four arable and five grassland soils which represent the range of soil textures and climatic conditions of the main agricultural areas in the UK were incubated at two different moisture contents (50 or 80% water holding capacity) and with or without inorganic fertiliser application (70 kg N ha −1 ammonium nitrate) over 22 days. Emissions of N2 O, CO2 and CH4 were measured twice per week by headspace gas sampling, and cumulative fluxes were calculated. Multiple regression modelling was carried out to determine which factors (soil mineral N, organic carbon and total nitrogen contents, C:N ratios, clay contents and pH) that best explained the variation in GHG fluxes. Clay, mineral N and soil C contents were found to be the most important explanatory variables controlling GHG fluxes in this study. However, none of the measured variables explained a significant amount of variation in CO2 fluxes from the arable soils. The results were generally consistent with previously published work. However, N2 O emissions from the two Scottish soils were substantially more sensitive to inorganic N fertiliser application at 80% water holding capacity than the other soils, with the N2 O emissions being up to 107 times higher than the other studied soils.